Enabling Early Sustainment Decisions Application to F-35 Depot-Level Maintenance - Drew, John G. (RAND Corporation, 2013)
To inform Air Force sustainment sourcing decisionmaking, RAND researchers adapted lessons from the transaction cost accounting literature to develop a framework that helps planners visualize sustainment data and compare new programs with legacy Air Force systems early in the acquisition process. This report demonstrates how the framework can be used to select among depot maintenance strategies by applying it to the F-35 Joint Strike Fighter.